IELTS Writing Test: Improving Cardinal Test Criteria for the Bangladeshi context (Journal of NELTA, 2018)
International English Language Testing System (IELTS) has become a widely used and globally accepted test for non-natives. It is conducted at more than a thousand centres in at least 130 countries (British Council, 2016), including 12 centres in Bangladesh (“Take IELTS test in or nearby Dhaka”, 2018). It also encompasses all four independent skills of the English language. Due to its popularity and effectiveness as a test, it is important to focus on assessment procedures of IELTS Writing tasks in the Bangladeshi context which is inconsistent with cardinal test issues. Thus, this article provides critical commentary on the IELTS writing test based on five cardinal issues for a proper test: reliability, validity, practicality, authenticity, and washback in connection with Bangladeshi as well as other similar ESL contexts. The documentary analysis of this article may help further research to enhance the utility of the IELTS writing test to measure ESL writing competence in a global context as an international test.